Neighborhood Psychosocial Stressors, Air Pollution, and Cognitive Function among Older U.S. Adults - Ailshire, Jennifer (Soc Sci Med, 2016)
A growing number of studies have found a link between outdoor air pollution and cognitive function among older adults. Psychosocial stress is considered an important factor determining differential susceptibility to environmental hazards and older adults living in stressful neighborhoods may be particularly vulnerable to the adverse health effects of exposure to hazards such as air pollution. The objective of this study is to determine if neighborhood social stress amplifies the association between fine particulate matter air pollution (PM(2.5)) and poor cognitive function in older, community-dwelling adults. We use data on 779 U.S. adults ages 55 and older from the 2001/2002 wave of the Americans’ Changing Lives study. We determined annual average PM(2.5) concentration in 2001 in the area of residence by linking respondents with EPA air monitoring data using census tract identifiers. Cognitive function was measured using the number of errors on the Short Portable Mental Status Questionnaire (SPMSQ). Exposure to neighborhood social stressors was measured using perceptions of disorder and decay and included subjective evaluations of neighborhood upkeep and the presence of deteriorating/abandoned buildings, trash, and empty lots. We used negative binomial regression to examine the interaction of neighborhood perceived stress and PM(2.5) on the count of errors on the cognitive function assessment. We found that the association between PM(2.5) and cognitive errors was stronger among older adults living in high stress neighborhoods. These findings support recent theoretical developments in environmental health and health disparities research emphasizing the synergistic effects of neighborhood social stressors and environmental hazards on residents’ health. Those living in socioeconomically disadvantaged neighborhoods, where social stressors and environmental hazards are more common, may be particularly susceptible to adverse health effects of social and physical environmental exposures.